Ireland : Financial Sector Assessment Program-Technical Note on Oversight of Fintech. (IMF Staff Country Reports; Country Report ;, 2022)
Ireland's fintech sector is growing in importance through the entry of innovative new players and digital transformation of incumbents' business models and products. The Irish Government has adopted an action plan for the development of Ireland's international financial services sector that includes several initiatives of relevance to fintech. Meanwhile, the Central Bank of Ireland (the Central Bank), the integrated financial services regulator, engages with new entrants with a view to securing consumer interests and safeguarding the resilience of the financial system, thereby harnessing the benefits of fintech while managing additional risks it may generate. The largest sub-sector is represented by payment and e-money institutions (PIEMIs). Recent data show most Irish adults are using digital payments multiple times a week, while 24 percent use their mobile phone for contactless payments. Ownership of crypto-assets is also on the rise, especially among young adults. Beyond payments and crypto-assets, fintech activities are developing on a smaller scale in areas such as insurance and investment management. Meanwhile, the importance of market support firms, including cloud service providers (CSPs), continues to grow.